Kedudukan Hukum Penguasa Fisik Garapan Terhadap Pihak Ketiga Berdasarkan Sertipikat - Hanifa, Marsya; Awiati, Wiwiek (UNES Law Review, 2023)
The dispute over ownership of land rights between PT Sentul City Tbk and 6000 residents of the physical rulers of arable land located in Bojong Koneng Village, Babakan Madang District, Bogor Regency due to claims from PT Sentul City Tbk who claimed to be the owner of land rights based on proof of ownership in the form of Building Use Rights Certificates however, PT Sentul City Tbk itself has never carried out activities on land while there are around 6000 residents who occupy and control physically and have never been raised objections or resistance from any party or from PT Sentul Citty Tbk for more than 50 (fivety) years. The purpose of the study was to find out how the legal position of the physical ruler is cultivated against certified third parties. The research method used is normative, the nature of the research used is descriptive-analytical, the type of data used is primary and secondary data, data analysis is carried out descriptively-qualitatively and quantitatively, and conclusion making is carried out with deductive logic. Ownership of land rights can be proven by the fact of physical control of land parcels for 20 (twenty) consecutive years or more, besides that the holder of a certificate of proof of rights in the form of building use rights is obliged to carry out construction and cultivate his land according to designation and is prohibited from abandoning land, if it occurs, the right to use the building will be erased.